2023
DOI: 10.1038/s41419-023-05843-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-grade human umbilical cord-derived mesenchymal stem cells improved skeletal muscle dysfunction in age-associated sarcopenia mice

Abstract: With the expansion of the aging population, age-associated sarcopenia (AAS) has become a severe clinical disease of the elderly and a key challenge for healthy aging. Regrettably, no approved therapies currently exist for treating AAS. In this study, clinical-grade human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) were administrated to two classic mouse models (SAMP8 mice and D-galactose-induced aging mice), and their effects on skeletal muscle mass and function were investigated by behavioral tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“… 8 , 9 , 23 This hypothesis is not corroborated by our observation of scattered MHC-II+ cells not preferentially associated with LC3+ or p62+ puncta. In addition, fast-twitching type II myofibers are mostly affected by impaired autophagy, 24 but could better survive increased activation of autophagy. The primary limitation of our study is the heterogeneous single cases of exceptionally rare neuromyophaties analyzed and, hence static morphologic assessment of autophagy instead of appropriate dynamic flux analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 , 23 This hypothesis is not corroborated by our observation of scattered MHC-II+ cells not preferentially associated with LC3+ or p62+ puncta. In addition, fast-twitching type II myofibers are mostly affected by impaired autophagy, 24 but could better survive increased activation of autophagy. The primary limitation of our study is the heterogeneous single cases of exceptionally rare neuromyophaties analyzed and, hence static morphologic assessment of autophagy instead of appropriate dynamic flux analysis.…”
Section: Discussionmentioning
confidence: 99%
“…On a different note, an innovative study by Wang et al [119] has revealed the potential of clinical-grade human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) in two models of age-related sarcopenia mice. hUC-MSC transplantation was noted to restore skeletal muscle strength and performance through the cells' roles in enhancing the expression of extracellular matrix proteins, activating satellite cells, enhancing autophagy, and impeding cellular aging.…”
Section: Stem Cell Therapiesmentioning
confidence: 99%
“…In order to investigate NMJ degeneration in relation to the onset of sarcopenia, a well-accepted sarcopenic animal model, SAMP8 against its control strain, SAMR1 without sarcopenia phenotype were used in this study (Wang et al, 2023). In SAMP8, grip strength peaked at 8 months and decreased significantly by 32.00% at 10 months (p < 0.001).…”
Section: Samp8 Was Validated As Sarcopenic Animal Model With Samr1 As...mentioning
confidence: 99%